2017
DOI: 10.1097/md.0000000000008087
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive stimulation during Macintosh direct laryngoscopy compared with McGrath Mac videolaryngoscopy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In comparison to Macintosh, the needed force to visualize the laryngeal opening is lesser and the applied pressure on tongue base is more uniformly distributed with video laryngoscopes. [20] In this study, insignificantly more frequent airway trauma and sore throat were encountered with Macintosh. This may be related to the relatively greater force required to visualize the laryngeal opening.…”
Section: Discussionmentioning
confidence: 66%
“…In comparison to Macintosh, the needed force to visualize the laryngeal opening is lesser and the applied pressure on tongue base is more uniformly distributed with video laryngoscopes. [20] In this study, insignificantly more frequent airway trauma and sore throat were encountered with Macintosh. This may be related to the relatively greater force required to visualize the laryngeal opening.…”
Section: Discussionmentioning
confidence: 66%
“…As postoperative sore throat is usually self-limiting and improves within a week, it is generally considered as a minor complication. The incidence of postoperative sore throat after McGrath® MAC videolaryngoscopic intubation was reported to be 5–45.4% [7, 1218], and its causes were multifactorial. In this study, when McGrath® MAC videolaryngoscope with size 3 MAC blade was used for tracheal intubation, no significant difference in the incidence of postoperative sore throat was observed between patients with the use of a malleable “hockey-stick” curved stylet and those without.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the incidence of postoperative sore throat after McGrath® MAC videolaryngoscopic intubation with a stylet was 9–45.4% with an average of about 25% [1215]. To test the ability of McGrath® MAC videolaryngoscopic intubation without a stylet to reduce this incidence to 5%, at least 49 patients were enrolled in each group, based on an alpha of 0.05 (two-tailed) and a beta of 0.2.…”
Section: Methodsmentioning
confidence: 99%